Sistem Informasi Pariwisata Pantai Berbasis Website di Kabupaten Minahasa Tenggara - Arifin, Ravi Haris Christofel; Langi, Yohanes A.R.; Lahipu, Dodisutarma; Ketaren, Eliasta (Jurnal Teknologi Komputer dan Informasi, 2025)
This research aims to design and develop a beach tourism information system based on a website to facilitate the effective dissemination of tourism information in Southeast Minahasa Regency. Despite its rich potential in beach tourism, the region still struggles to provide comprehensive and accessible information for tourists. The research adopts the prototype method, involving users throughout the system development stages, including planning, design, construction, and evaluation. The developed system features tourist destination information, photo galleries, visitor reviews, and an admin page for content management. Testing using the black box method shows that the system performs its intended functions properly. This system is expected to enhance local tourism promotion and provide tourists with fast, accurate, and engaging access to beach tourism information.